If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) + 9 = 2(x + 4) Reorder the terms: 3(-2 + x) + 9 = 2(x + 4) (-2 * 3 + x * 3) + 9 = 2(x + 4) (-6 + 3x) + 9 = 2(x + 4) Reorder the terms: -6 + 9 + 3x = 2(x + 4) Combine like terms: -6 + 9 = 3 3 + 3x = 2(x + 4) Reorder the terms: 3 + 3x = 2(4 + x) 3 + 3x = (4 * 2 + x * 2) 3 + 3x = (8 + 2x) Solving 3 + 3x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 3x + -2x = 8 + 2x + -2x Combine like terms: 3x + -2x = 1x 3 + 1x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 1x = 8 + 0 3 + 1x = 8 Add '-3' to each side of the equation. 3 + -3 + 1x = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 8 + -3 1x = 8 + -3 Combine like terms: 8 + -3 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| (3y-7)=(2y+4) | | 3y+12=27 | | 6z+9=6z-z | | 17x-(8x-2)=74 | | 15=6+9(x-6) | | (5x)=(3x+18) | | 2(x+2)=18 | | 5x=(x+18) | | x^4-9x^3+21x^2-x-30=0 | | x^4-9x^3-21x^2-x-30=0 | | 32=0.66x-34 | | x^3-4x^2-3x+12=0 | | 9(2x-8)=3(6x+9) | | 15=9-6x | | (4y)+(3y)=180 | | .5x=1.45 | | (3x-18)+(2x+12)=180 | | 2(2)+4=2x | | 3a-3(7+5a)=9(2+a) | | (4y)+(3x-18)+(3z)+(2x+12)=360 | | 2(2)+4=x | | 12x-25=6x+15 | | (19x-17)-(3x-72)= | | 8(120)=x | | 8(15)=y | | 7+2t-4=8t+11-5t | | 2x-15=5x | | 6x+2=4x+12 | | 4x+63=14x-7 | | -3(x+5)=-27 | | 9x+17=5x+13 | | 6(2x+3)=66 |